George C. Williams and Evolutionary Literacy - Cohen, Michael P. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
In this book, a case study of a humanistic reading of an essential evolutionary theorist, George C. Williams (May 12, 1926-September 8, 2010), the author contends that certain classic works of evolutionary theory and history are the most important nature writing of recent times. What it means to be scientifically literate-is essential for humanistic scholars, who must ground themselves with literary reading of scientific texts. As the most influential American evolutionary theorist of the second half of the twentieth century, Williams masters critique, frames questions about adaptation and natural selection, and answers in a plain, aphoristic writing style. Williams aims for parsimony-to "recognize adaptation at the level necessitated by the facts and no higher"-through a minimalist writing style. This voice articulates a powerful process that operates at very low levels by blind and selfish chance at the expense of its designed products, using purely trial and error. Michael P. Cohen works at the intersection of literary theory and nature writing. His books include Pathless Way: John Muir and American Wilderness (1984), A Garden of Bristlecones: Tales of Change in the Great Basin (1998) and Granite and Grace: Seeking the Heart of Yosemite (2019). .
Introduction: The Face of the Adaptationist Program -- Chapter 1. A Balance of Forces: Homes and Schools, Genes, Senescence, and Altruism -- Chapter 2.Design, Parsimony, and a Critique of Adaptation -- Chapter 3.Opening Sociobiology: Disciplining the Plain Style -- Chapter 4.Sex, Death, and the Language of Sociobiology -- Chapter 5.How Scientific Reductionism leads to Evolutionary Explanation -- Chapter 6.Evolution and Human Ethics: An Expansion from Sociobiology -- Chapter 7.History, Natural Selection, and the Book of Nature -- Chapter 8.Repairing Human Natures -- Chapter 9.The Dark Side of Biology -- Chapter 10.How Shall a Human Face Death.
Keywords: Literature, Modern-20th century; Ecocriticism; America-Literatures.; Human ecology-History.; Science-History.; Communication in science; Twentieth-Century Literature; Ecocriticism; North American Literature; Environmental History; History of Science; Science Communication